MARITAL STATUS ROLE IN DELAYED ANTENATAL CARE INITIATION AMONG INDONESIAN MADURESE - Rohmah, Nikmatur; Laksono, Agung Dwi (JURNAL KESEHATAN REPRODUKSI, 2024)
Background: The diversity of marital status in Madura, influenced by the socio-cultural context, has the potential to cause delays in initiating ANC visits. Objective: The study aimed to explore the role of marital status in delayed Antenatal Care (ANC) initiation among Madurese women in Indonesia. Method: The secondary analysis utilized the 2023 Indonesian Health Survey data. The study analyzed 551 women who delivered babies within the last five years. In addition to delayed ANC initiation as the outcome variable and marital status as the exposure variable, we examined eight control variables: regency, residence, age, education, employment, wealth, insurance, and parity. Binary logistic regression was employed in the final analysis. Results: The findings indicate that 23.3% of Indonesian Madurese women delayed ANC initiation. Currently, 3.2% of Madurese women are either divorced or widowed.  In terms of marital status, divorced/widowed Indonesian Madurese women are likely 5.726 times more to have delayed ANC initiation than those married group (95% CI 5.432-6.035). Moreover, the study found eight control variables associated with delayed ANC initiation: regency, residence type, age group, marital status, education level, employment, wealth, health insurance ownership, and parity. Conclusion: The study concluded that marital status was associated with delayed ANC initiation among Indonesian Madurese women. Divorced/widowed Madurese women were likely five times more to have delayed ANC initiation than married women.